A randomised crossover trial of the acute effects of a deep-fried Mars bar or porridge on the cerebral vasculature. Issue 4 (November 2014) - Dunn, William G; Walters, Matthew R
Introduction: The deep-fried Mars bar has been cited as 'all that is wrong with the high-fat, high-sugar Scottish diet'. We investigated the effect of ingestion of a deep-fried Mars bar or porridge on cerebrovascular reactivity. We hypothesised that deep-fried Mars bar ingestion would impair cerebrovascular reactivity, which is associated with increased risk of ischaemic stroke. Methods: Twenty-four fasted volunteers were randomised to receive a deep-fried Mars bar and then porridge (control), or vice-versa. We used transcranial Doppler ultrasound to calculate Breath Holding Index as a surrogate measure of cerebrovascular reactivity. Change in Breath Holding Index post-ingestion was the primary outcome measure. Results: Twenty-four healthy adults (mean (SD) age 21.5 (1.7) years, 14 males) completed the protocol. Deep-fried Mars bar ingestion caused a non-significant reduction in cerebrovascular reactivity relative to control (mean difference in absolute Breath Holding Index after deep-fried Mars bar versus porridge −0.11, p  = 0.40). Comparison of the difference between the absolute change in Breath Holding Index between genders demonstrated a significant impairment of cerebrovascular reactivity in males (mean difference women minus men of 0.65, 95% CI 0.30 to 1.00, p  = 0.0003). Conclusion: Ingestion of a bolus of sugar and fat caused no overall difference in cerebrovascular reactivity, but there was a modest decrease in males. Impaired cerebrovascular reactivity is associated with increased stroke risk, and therefore deep-fried Mars bar ingestion may acutely contribute to cerebral hypoperfusion in men.